Coupled Processes Associated With Nuclear Waste Repositories 1987
DOI: 10.1016/b978-0-12-701620-7.50025-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Diffusion in Compacted Montmorillonite Engineered Barriers

Abstract: The bentonite-based engineered bar rier or packing is a proposed component of several designs conceived to dispose of high-level nuclear waste in geologic reposi tories. Once radionulcides escape the waste package, they must first diffuse through the highly impermeable day-rich barrier before they reach the host repository. To deter mine the effectiveness of the packing as a sorption barrier in the transient release period and as a mass-transfer barrier in the steady release period over the geologic time scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Since the permeabilities of potential geological sites and packing materials are very low ( K Om') (Rolfe & Alymore, 1977;Seitz & Couture, 1983) ground water velocities in the repository are small (< 1 m a - ' Anderson et al, 1982;Neretnieks, 1982. This results in nuclide release that is diffusion-controlled (Jahnke, 1987;Jahnke & Radke, 1987). In this paper we measure diffusion rates of non-radioactive Cs' and Sr' +, two important analogues of long-lived and harmful radioisotopes in high-activity nuclear waste canisters, through Na-montmorillonite, the major component of bentonite.…”
mentioning
confidence: 96%
“…Since the permeabilities of potential geological sites and packing materials are very low ( K Om') (Rolfe & Alymore, 1977;Seitz & Couture, 1983) ground water velocities in the repository are small (< 1 m a - ' Anderson et al, 1982;Neretnieks, 1982. This results in nuclide release that is diffusion-controlled (Jahnke, 1987;Jahnke & Radke, 1987). In this paper we measure diffusion rates of non-radioactive Cs' and Sr' +, two important analogues of long-lived and harmful radioisotopes in high-activity nuclear waste canisters, through Na-montmorillonite, the major component of bentonite.…”
mentioning
confidence: 96%
“…It has been reported that some cations diffuse through aggregated materials such as bentonite or in fractured media like whole rock at greater rates than those predicted from aqueous phase diffusion alone (Kim et al 1993;Jahnke and Radke 1987;Bradbury et al 1986;Skagius and Neretnieks 1985;Rasmuson and Neretnieks 1983). Surface diffusion has been invoked to explain this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Omitting the κ subscript, D is described by the equations Equation 18 accounts for surface diffusion, which can be responsible for significant transport in strongly sorbing media (Moridis 1999;Cook 1989). The surface diffusion flux is given by Jahnke and Radke (1987) as (Bird et al 1960, p. 514), as …”
Section: Equations Of the Flux Termsmentioning
confidence: 99%